A literature discussion and research gap identification on role, art activity and economy: a relationship between artist, gallery, and buyer from the Islamic perspective / Nur Adibah Nadiah Mohd Aripin ... [et al.] - Mohd Aripin, Nur Adibah Nadiah; Ramli, Ishak; Mohamad, Noor A'yunni; Arshad, Mohd Fawazie; Desa, Noor Enfendi (Universiti Teknologi MARA, Perak, 2023)
Visual art is dynamically developed in Malaysia. The opening of many art galleries shows that people are more receptive to the visual arts as a part of their community. These collisions create the art sector as a career field. This phenomenon encouraged artists to exhibit their artworks in the gallery and economically increased the numbers of art collectors as buyers to support the art scene and build a new bridge of connection between artist, gallery, and buyer. There is interest growing yet little research in this area has been discovered. This research is to identify the relationship between the artist, gallery, and buyer which is related to the role, art activity involved, and economic factors based on the Islamic perspectives. These relations are common and have become the norm in the social environment of visual arts. Furthermore, the role, art activity involved, and economic factor between the relationship of the artist, gallery, and buyer is rarely been discussed. The gap identification will occur by using the qualitative method through observations on the content analysis. This research has the potential to extend the understanding of the relationship between the artist, gallery, and buyer from the Islamic perspective.